Capturing validating personalization requirements in web applications - Robles Luna, Esteban
Personalization is a key feature to improve user experience in Web applications therefore many Web engineering approaches allow the specification of some type of personalization when modelling a website. However, these approaches usually neglect the process of capturing representing personalization requirements, thus not considering them when the application evolves; maintenance of these requirements is then a very complex task. In this paper, we present WebSpec, a requirement artefact used to capture navigation, interaction interface aspects of Web applications. Concretely, we focus on how to specify personalization requirements, on how to automatically generate the personalization model their specification. Furthermore, the requirements specification we derive a set of interaction tests to assess the personalization functionality. We illustrate our ideas with an E-commerce application example describe a prototype tool which implements the described functionality.